Introduction - McKeown, M; Nuti, A (Global Justice Network, 2016)
Consider the global distribution of wealth. A 2016 OXFAM report revealed that 62 people hold as much wealth as half the world’s population. Global wealth distribution is not simply a question of unequal shares across individuals, but also one of class. Liberal theory often seeks to redress this state of affairs through global redistribution on an individual basis. But is it enough to call for redistribution of wealth and resources, or must we interrogate the underlying power relations first? What are the preconditions for redistribution? Are capitalist economic relations that create and sustain this system sufficiently exposed or critiqued? Consider the global distribution of wealth. A 2016 OXFAM report revealed that 62 people hold as much wealth as half the world’s population. Global wealth distribution is not simply a question of unequal shares across individuals, but also one of class. Liberal theory often seeks to redress this state of affairs through global redistribution on an individual basis. But is it enough to call for redistribution of wealth and resources, or must we interrogate the underlying power relations first? What are the preconditions for redistribution? Are capitalist economic relations that create and sustain this system sufficiently exposed or critiqued?